Estimating the fundamental value of sports clubs and stadia: Application to Panathinaikos FC and Leoforos - Bertsatos, Georgios; Sapountzoglou, Gerassimos (Review of Economic Analysis, 2025)
We propose a fundamental valuation model for sports clubs and stadia using discounted (adjusted) revenues. We argue that a sports club is a “quasi firm” that aims to balance budgets, achieve an efficient allocation of financial resources, and maximize revenues. Under this objective the sports club’s welfare and value are maximized. Then we offer a method for estimating the value of a sports club’s stadium. The proposed valuation model can be useful during acquisition negotiations or for assessing managerial performance. Combining the proposed model with stochastic Monte Carlo simulations, we estimate the brand-name value and the club’s total value of the football team of Panathinaikos, as well as the value of its iconic home ground, Apostolos Nikolaidis Stadium (known as Leoforos) located in the heart of Athens at Alexandra’s Avenue